If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 9y = 11 Solving -10x + 9y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9y' to each side of the equation. -10x + 9y + -9y = 11 + -9y Combine like terms: 9y + -9y = 0 -10x + 0 = 11 + -9y -10x = 11 + -9y Divide each side by '-10'. x = -1.1 + 0.9y Simplifying x = -1.1 + 0.9y
| 6x^4-12x^3=0 | | 3p=29.1 | | h-25=36 | | 3k+2(3k+2)=49 | | 2x+12+38=80 | | 5v^2-11v-12=0 | | -5x+2y=-14 | | 0.66+1=4x-0.33 | | -4(n+7)-6n=-98 | | -5x-3=-20 | | 6n+8(n+3)=-2(2+2n)-8 | | 5=6w-9w-1 | | 16+3x+38=96 | | 16+3x+38+96=180 | | 7+4(1-4a)=-12+7a | | 5=6w-8w-1 | | x+0.1x=.017 | | 16x+3x+38=96 | | X^2+y^2+6X+2y+6=o | | -25=-10+1p | | 2p-5+7p=19+5p | | 2+5y=-3 | | 5y+3=3y-1 | | -5x+7y=1 | | 2r+2(5r+6)=-6+6r | | (4x-6)(8x+2)=0 | | (2x+3)(3x^2+2x-5)= | | 12y+180+6x=180 | | 138=-3(6n+2) | | x+3=152 | | 9s+3=67 | | 9x+7y=100 |